'In considerable variety' introducing the diversity of Australia's insects - New, Tim R. (Springer eBooks., 2011)
Many conservationr managers lack entomological training and the perspective needed to conserve insects within their areas of responsibility. Using Australian insect examples this book provides an introduction to basic entomology and emphasises the massive taxonomic, ecological and evolutionary diversity within this fauna, together with its interactions with humanity.  It is written largely in non-technical language, to provide accessible information on many aspects of insect natural history and the importance of their diversity and conservation, and contains suggestions for further reading to expand on the themes introduced.